Public Opinion on Measures for Improvement in Air Quality with special reference to Chennai - Qays, M I Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The World Health Organization defines pollution as “the presence of materials within the air in such concentration that area unit harmful to man and his surroundings. The objectives of the study are to analyse the difference between the precautionary actions of polluted air and gender and to find the association between major cause of toxic air in the atmosphere and age of the respondents. For the purpose of this study is descriptive research is used to portray accurately the public opinion on measures for improvement in air quality. Convenient sampling method is used to collect the samples. 1640 samples were collected for the research. Dependent variables are prevention of polluted air, causes of toxic air in atmosphere, renewable energy, public transport and car pooling, CNG and electric vehicles, solar power, sustainable products. Independent sample t test, Chi square and ANOVA are the research tools used in this research. It was found that there is significant association between major cause of toxic air in the atmosphere and age of the respondents. It also shows that there is difference between the precautionary actions of polluted air and gender. We must always conjointly seriously think about energy and renewable energy use to scale back pollution. To reduce the pollution in the atmosphere we can take certain steps like reducing the number of trips in personal vehicles, avoid burning of trash, reduce the use of wood stove etc.